Restitution Exhibitions: Issues of Ethnic Identity and Art - Greenberg, Reesa (Intermédialités / Intermediality, 2010)
This essay looks at post 2005 restitution exhibitions of art believed or known to be owned by Jews stolen during National Socialist times in order to examine complex questions and layered relationships involving private property, public institutions and museum display.